1985
DOI: 10.1111/j.1574-6968.1985.tb00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical sterilization of microbial cells by semiconductor powders

Abstract: We report the novel concept of photochemical sterilization. Microbial cells were killed photoelectrochemically with semiconductor powder (platinum‐loaded titanium oxide, TiO2/Pt). Coenzyme A, (CoA) in the whole cells was photo‐electrochemically oxidized and, as a result, the respiration of cells was inhibited. Inhibition of respiratory activity caused death of the cells. Lactobacillus acidophilus, Saccharomyces cerevisiae and Escherichia coli (103 cells/ml respectively) were completely sterilized when they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
416
0
9

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,297 publications
(431 citation statements)
references
References 7 publications
6
416
0
9
Order By: Relevance
“…Matsunaga et al (44,45) Once formed, these highly reactive radical species seem to play a key role in promoting the indirect oxidation of organic substances (Eqs. 9-11, Scheme 3).…”
Section: Mechanisms Of Self-disinfection Activity On Tiomentioning
confidence: 99%
“…Matsunaga et al (44,45) Once formed, these highly reactive radical species seem to play a key role in promoting the indirect oxidation of organic substances (Eqs. 9-11, Scheme 3).…”
Section: Mechanisms Of Self-disinfection Activity On Tiomentioning
confidence: 99%
“…There are some different opinions about the bactericidal mechanisms of these photocatalysts. In the early studies, Matsunaga et al 1,2 proposed that the direct oxidation of coenzymes in TiO 2 -treated cells, which led to the decrease in respiratory activities, was the reason for cell death. Recently, it was proposed that the destruction of the cell structure resulted in cell death.…”
Section: Introductionmentioning
confidence: 99%
“…1 Since then, numerous studies related to the bactericidal effect of TiO 2 photocatalysts have been reported. [2][3][4][5][6][7][8][9][10] TiO 2 photocatalysts have also been applied to inactivate bacteria, viruses, and cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The nanocrystalline Bismuth Tungstate materials have been successfully synthesized using Bi(NO 3 ) 3 .5H 2 O and Na 2 WO 4 .2H 2 O as a starting material by microwave assisted hydrothermal process. The synthesized materials are in nano form having crystallite size of ~ 24 nm.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies on TiO 2 photocatalyst have been done by different scientists. In 1985, Matsunaga et al studied on photochemical sterilization of microbial cells by semiconductor powders [3]. Then research further broadens the scope of semiconductor photocatalysis.…”
Section: Introductionmentioning
confidence: 99%